BENTUK DAN PESAN DALAM IKLAN CONTREX FORMS AND MESSAGES IN CONTREXADVERTISING - Ghifar Dimas Harkami; Muhammad Hasyim; Irianti Bandu (Journal of Innovation Research and Knowledge, 2023)
This research aims to described the form of and messages in image advertising. Besides, the writer also would like to identify and analyze the form and the messages specifically in the Contrex Advertising. This study used descriptive-qualitative method with a semiotic approach. The source of data in this research taken from Contrex mineral water advertisements advertised in digital or internet from various websites. The analytical method used is the semiotic theory by Roland Barthes. The results the research showed that the form of signs displayed by advertisers in conveying advertising forms and messages. The writer found out that advertisers presented two types of signs, which are found in form of Visual (Images, Colors, and Design) and in form of Verbal ( Sentences, Phrases, and Words). All issues depicted in each advertisement raise the issue of ideal body shape and healthy lifestyle. The meaning of each advertisement is supported by news and related articles that have been published in Indonesian or French media